Introduction to Leadership / Concepts and Practice (Northouse Peter G Sage, 2009)
This book focuses on providing readers with practical strategies for becoming better leaders. Preface, About the Author, Being a Leader, Recognizing Your Traits, Recognizing Your Philosophy and Style of Leadership, Attending to Tasks and Relationships, Developing Leadership Skills, Creating a Vision, Setting the Tone, Listening to Out-Group Members, Overcoming Obstacles, Addressing Ethics in Leadership, Index, Questionnaires.